2022
DOI: 10.1007/s13346-022-01238-y
|View full text |Cite
|
Sign up to set email alerts
|

A review of formulations and preclinical studies of inhaled rifampicin for its clinical translation

Abstract: Inhaled drug delivery is a promising approach to achieving high lung drug concentrations to facilitate efficient treatment of tuberculosis (TB) and to reduce the overall duration of treatment. Rifampicin is a good candidate for delivery via the pulmonary route. There have been no clinical studies yet at relevant inhaled doses despite the numerous studies investigating its formulation and preclinical properties for pulmonary delivery. This review discusses the clinical implications of pulmonary drug delivery in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 168 publications
0
4
0
Order By: Relevance
“…Several anti-TB drugs have been researched for their inhalable formulation using in vitro and in vivo studies. These studies inform that inhaled drugs for TB treatment assure therapeutic benefits by delivering drugs directly to the lungs at higher concentrations (Khadka et al, 2022).…”
Section: Formulations Of Inhaled Microspherementioning
confidence: 93%
See 1 more Smart Citation
“…Several anti-TB drugs have been researched for their inhalable formulation using in vitro and in vivo studies. These studies inform that inhaled drugs for TB treatment assure therapeutic benefits by delivering drugs directly to the lungs at higher concentrations (Khadka et al, 2022).…”
Section: Formulations Of Inhaled Microspherementioning
confidence: 93%
“…TB therapy is recommended with regimens of four anti-TB first-line drugs for six months, which are isoniazid (INH), rifampin (RIF), ethambutol (ETH), and pyrazinamide (PZA) (Khadka et al, 2022). They are prescribed during the first two months of treatment and continued for the next four months with rifampicin and isoniazid only.…”
Section: Introductionmentioning
confidence: 99%
“…By 1968, it was clear that rifampin had an important role in therapy for mycobacterial infections [12]. Rifampin is delivered orally [15.16], intravenously [16], topically [17], by inhalation for pulmonary mycobacterial infection [18,19], as eye drops [20] and as nose drops [21,22].…”
Section: Rifampinmentioning
confidence: 99%
“…Recently several papers were published devoted to the inhaled liposomal form of some antituberculosis drugs such as rifampicin [17,18]. An in vivo test with small animals reported that almost 65% of the dose was achieved in the lungs.…”
Section: Introductionmentioning
confidence: 99%